TALABALARDA MA’NAVIY-AXLOQIY TAFAKKURNI SANOGEN TARBIYALASHDA PEDAGOGNING KASBIY KOMPETENTLIGI MASALASI XORIJ TAJRIBASIDA - Sabirova, Ch.A. (SCIENCE and SOCIETY, 2024)
In this article, the fundamentals of professional competency issues of the pedagogue in healthy education of spiritual and moral thinking of students are explained.
Keywords: student; spiritual and moral education; spiritual and moral thinking; educational process; healthy education; spiritual and moral values; self-analysis; self-evaluation and self-change